From Supply Chain Connectivity (SCC) to Supply Chain agility (SCA), Adaptability and Alignment: Mediating Role of Big Data Analytics Capability - Thammarak Srimarut; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
The main aim of the current study is to analyze the effect of SCC on the large information analysis capability and to analyze the impact of this big data analytics capability on the agility, adaptability and alignment of the supply chain. For this purpose, the current study used RBV as supporting the idea because the idea of RBV suggests that a firm can build its capabilities based on its resources. The data for the current study was collected from 300 employees of manufacturing firms of Thailand through questionnaires and the sample was selected through purposive sampling technique. The analysis and results revealed that SCC has a significant positive role in building big data analytics capability of the firm. Furthermore, it has been found that big data analytics capability enhances the SC qualities to cope with external environment and fluctuations because it significantly positively influences the SCA, adaptability and alignment. The current study and its findings have implications in practice as well as theory because they are expected to make value contributions in both fields.